Comprehensive Treatment and Vascular Architecture Characteristic of High-Flow Vascular Malformations in Periorbital Regions. Issue 1 (January 2021) - Yang, Peng; Ren, Jian; Yu, Jia-Xing; Zhai, Xiao-Dong; Hu, Peng; Hong, Tao; Zhang, Hong-Qi
Abstract : Objective: This study analyzed the vascular architecture characteristics of high-flow vascular malformations (VMs) in periorbital regions, as well as the treatment and imaging prognosis of occlusion degree of the outflow veins. Method: The clinical data of 24 patients with high-flow VMs in periorbital regions treated in our center from 2012 to 2019 were analyzed retrospectively, and the vascular architecture characteristics, treatment methods, and follow-up results were recorded. Results: The vascular architecture of high-flow VMs in periorbital regions which usually contained the intracranial feeding arteries (24/24, 100.0%) and intracranial outflow veins (18/24, 75.0%). The average age of first diagnosis was 23 ± 16 years; the average age of treatment was 37 ± 10 years; the median follow-up time was 42.5 months. Twenty-four patients with high-flow VMs in periorbital regions had 58 treatments in all. The imaging cure was achieved in 6 patients by complete occlusion of outflow veins, and no recurrence was found by DSA. Eighteen patients who get incomplete occlusion of outflow veins were given 49 treatments, and 8 patients had imaging recurrence. Seven patients (7/24, 29.2%) had treatment-related complications in all. Conclusions: Patients with high-flow VMs in periorbital regions are the most complex cases. The prognosis of patients whose outflow veins can be completely occluded is relatively good. The stepwise embolization while preserving organ function is advisable. Nevertheless, the incidence of treatment complications is still high. Abstract : Supplemental Digital Content is available in the text